Synthesis and Characterization of Core-Shell Nanocrystals of Co-Rich Cathodes. Issue 5 (1st January 2020) - Kwon, Bob Jin; Dogan, Fulya; Jokisaari, Jacob R.; Key, Baris; Bolotin, Igor L.; Paulauskas, Tadas; Kim, Chunjoong; Klie, Robert F.; Cabana, Jordi
Abstract : Interfacial stability between the cathode and the electrolyte in Li-ion batteries directly determines durability upon cycling. Core-shell nanoscale heterostructures offer high precision when replacing redox-active ions on the surface with inactive species such as Al ions to suppress these deleterious reactions. However, the level of compositional complexity of leading cathodes for high-energy devices, while showing increased stability, remains to be demonstrated for these heterostructures. A combination of colloidal synthesis and subsequent post-annealing process was used to produce cores of LiCo0.5 Ni0.25 Mn0.25 O2, a layered oxide with a high theoretical capacity, with epitaxial and conformal shells with increasing concentration of Al from the interior to surface. Thorough insight at high chemical and spatial resolution was obtained by a combination of characterization techniques. The gradient of Al was controlled by the initial content and the temperature of synthesis. The passivation layers play a critical role in notably increasing the retention of capacity, which was particularly considerable under harsh conditions such as wide potential window and, especially, elevated temperature, which accelerate side reactions. Spectroscopic analysis revealed that the tailored surface layers mainly stabilized the electronic environment at the surface, suggesting a possible explanation to the improved battery performance.